2018
DOI: 10.1002/hsr2.32
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone, cortisol,hGH, andIGF‐1 levels in anItalianfemale elite volleyball team

Abstract: PurposeTo assess the transferability of the reference intervals (RI) of testosterone (T), cortisol (C), human growth hormone (hGH), and insulin‐like growth factor (IGF)‐1, calculated on a normal healthy population, to a population of female elite volleyball players. Secondary aim of this study is the evaluation of the T/C ratio as predictive tool of overtraining during the annual regular season.MethodsA retrospective, longitudinal, observational study was performed, enrolling 58 professional female volleyball … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 38 publications
2
16
1
1
Order By: Relevance
“…Although previous studies identified a significant stimulatory effect of exercise (Schwarz et al, 1996;Gregory et al, 2013;Hackney et al, 2016) and training of female athletes (Roli et al, 2018) on serum IGF-1 levels, our data showed no significant differences in either IGF-1 and IGFBP-3 in response to graded exercise. In the present study, post-exercise cortisol levels seem to stimulate higher IGF-1 levels, whereas higher T/C levels correspond to lower hGH and IGF-1 secretion.…”
Section: Discussioncontrasting
confidence: 93%
See 3 more Smart Citations
“…Although previous studies identified a significant stimulatory effect of exercise (Schwarz et al, 1996;Gregory et al, 2013;Hackney et al, 2016) and training of female athletes (Roli et al, 2018) on serum IGF-1 levels, our data showed no significant differences in either IGF-1 and IGFBP-3 in response to graded exercise. In the present study, post-exercise cortisol levels seem to stimulate higher IGF-1 levels, whereas higher T/C levels correspond to lower hGH and IGF-1 secretion.…”
Section: Discussioncontrasting
confidence: 93%
“…It should be stated that the intense treadmill exercise to volitional exhaustion elicited a time-dependent increase of IL-6 during recovery, but did not alter serum IL-1β and TNF-α concentration. Previous studies support the findings that exercise which induces gene expression of inflammatory markers (acute phase cytokines) and their signaling pathways may constitute a sensitive tool to characterize the early effects of exercise on immune regulation (Pedersen and Hoffman-Goetz, 2000;Radom-Aizik et al, 2009) and adaptive processes during exercise (Ostrowski et al, 1999;Gillum et al, 2011;Roli et al, 2018). Physical stress causes the deregulation of muscle homeostasis and fiber integrity.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…There is recent evidence that sex hormones may have an impact on susceptibility to occurrence of various arrhythmias. It has been shown that elite female athletes have significantly higher values of testosterone, when compared to controls [ 22 ]. Our group has recently shown that circulating sex hormone levels, particularly high levels of testosterone and low levels of estrogen, may lead to adverse arrhythmic outcomes in ARVC.…”
Section: Discussionmentioning
confidence: 99%